ANALISIS PERKEMBANGAN KEMAMPUAN KEUANGAN DAERAH DALAM MENDUKUNG PELAKSANAAN OTONOMI DAERAH DI KABUPATEN NATUNA (Tahun Anggaran 2009-2013) - Gustra Arianda; Nurazlina '; Mudrika Alamsyah Hasan (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2014)
This research aims to analys the progress of district finance ability tosupport the autonomy of natuna among 2009-2013.The type of thies research is descritive comparative. Data of this researchare based on APBD and then analys by the ratio of local financial autonomy, the degree of fiscal decentralization, routine ability index, the ratio of harmony and growth ratios.Based on the results of the analysis has been done obtained thefollowing results: Based on the ratio of local financial autonomy was performe the ability to pay a goverment programe, development and service to the society that have paid tax and retibution as a source of income of the district. the ratio of local financial autonomy is 2.11%. It meant the value of the ratio of local financial autonomy is too low. The degree of fiscal decentralization of Natuna District among 5 years is average of 2.70%. it meant the ability of Natuna ability goverment to increasing PAD and pay the expences of development still bad. Routine ability index ratio of Natuna District among 5 years is average of 2.73%.It meant the value of the Routine ability index ratio is too low. The ratio ofharmony have a result that routine expenditure is bigger than the development expenditure. It meant the goverment's fund still priorited to support a routine expenditure, so that the development expenditure will be small relatively. While growth ratios desciptive an ability iof district goverment to proof and increase the success from period to another period. Growth ratios among 5 years are 3 times positive growth suce as 2011, 2012 and 2013 but once negative growth in 2010.Key Word : ratio of local financial autonomy, the degree of fiscaldecentralization, routine ability index, the ratio of harmony and growthratios.